(3GdEOGQI hGdCYeGds - (3UGdM egOj eMSf(B, (3GdYGeQjs; (3GdZGdHj WGgQ eMSf efUhQ(B, s ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2007)
(3jVe gPG GdcJGH (B: (3GdHGH GdChd (B: (3eONd Edi GdGOGQI eaGgje GdGOGQI hGdGYeGd aj YGde hGMO , GdGOGQI Hjf GdeGVj hGdMGVQ ,CNdGbjGJ GdGYeGd hGdeSDhdjI GdGLJeGYjI ddefXeGJ GdHGH GdKGfj (B: (3HjFI GdEOGQI hGdCYeGd GdHjFI KbGaI GdefXeI hGdJfhY , GOGQI GdGYeGd aj Xd GdYhdeI , GdQHGOI hGdGHOGY hGdGYeGd GdUZjQI GdHGH GdKGdK (B: (3GdJNWjW hGJNGP GdbQGQ GdJNWjW hUjGZI GdGgOGa , GdQbGHI , GdGOGQI GdGSJQGJjLjI, GJNGP GdbQGQGJ hOhQ JcfhdhLjG GdeYdheGJ GdHGH GdQGHY (B: (3GdJfXje CSGSjGJ GdJfXje , JUeje GdefXeGJ , GdJZjQ hGdJWhQ aj GdefXeGJ GdHGH GdNGeS (B: (3GdbjGOI CSGSjGJ GdbjGOI , GdJMajR hHfGA aQb GdYed , GdGJUGdGJ GdHGH GdSGOS (B: (3hXGFa GdefXeI EOGQI GdGfJGL hGdYedjGJ , GdJShjb , EOGQI GdehGQO GdHTQjI , GdGOGQI GdeGdjI hGdeMGSHjI , hXGFa efXejI CNQi GdHGH GdNGeS GdbjGOIs
(3HjHdjhZQGajG(B: (3U(B.660 -662s
Keywords: (3EOGQIs; (3EOGQI GdCYeGds; (3GdefXeIs